PENDIDIKAN ISLAM DAN PENINGKATAN SUMBER DAYA PEREMPUAN - Eniwati Khaidir (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2010)
Education has a very strategic function in order to improve the quality of the human resources. To realize it, it is not possible only charged one of its human resources namely men, while female resources are ignored. On the other side, Islamic education is faced with the challenge of modern life which is full with complex issues, such as how Islamic education capable of preparing quality of human in the face of societal change, so that the products of Islamic education not only serves the need for hereafter, but should be able to compete in a competitive and proactive of modern world. This article discusses whether women's resources can be enhanced through Islamic education and what must be done to make Islamic education as an effort to increase women’s resources